BLYNK-BASED REMOTE LIGHT CONTROL WORKSHOP FOR VOCATIONAL / HIGH SCHOOL STUDENTS IN PURWAKARTA - Dani Usman; Aziz Yulianto Pratama; Nurriza Kholifatulloh Hasanah; Purwandito Tulus Asmoro; Dieta Wahyu Asry Ningtias; Feri Siswoyo Hadi Santoso; Iwan Setiawan; Danang Hendrawan (Jurnal Abdisci, 2025)
Background. Community service activities, including a Blynk-Based Remote Light Control Workshop, were held on October 14, 2024, at the Indorama Engineering Polytechnic, Purwakarta. This activity is intended for SMK/SMA students in the Purwakarta area and aims to introduce Internet of Things (IoT) technology and its application in daily life. Aim. In this workshop, participants were given an understanding of the basic concepts of IoT and trained to create a simple project, namely the remote control of lights using the Blynk application and the NodeMCU microcontroller. Methods. The training sessions include introducing the Blynk app, user interface settings, and how to connect electronic devices to the internet network. This activity is carried out interactively, combining theory and hands-on practice. Result. The activity results show that students can understand the basic concepts of IoT and successfully create a light control project independently. The high enthusiasm of the participants is an indicator of the workshop's success in increasing students' interest and skills in the field of IoT technology. Implementation. This activity is expected to motivate students to continue to develop their technical skills and foster awareness of the importance of technological innovation in the digital era.